Correlations and path analysis of yield components in cowpea - Santos,Adriano dos (2014)
Obtaining correlations and direct and indirect effects of yield components is important for the selection of promising parental and segregating populations. The objective of this research was to estimate the genotypic and phenotypic correlations, and to analyze the direct and indirect effects of yield components on grain yield in 20 cowpea (Vigna unguiculata) genotypes. The experimental design was in randomized blocks with 20 treatments and 4 replications. The character showed low to moderate possibility of gain from indirect selection, with greater possibility for success when joining multiple character and a genotype of better performance.